Fabricated Narrations in the Asbāb al-Nuzūl of the Qur’an: An Analytical Study: https://doi.org/10.5281/zenodo.17203179 - Raznan Bibi; Dr. Ziaullah al-Azhari (Journal of Religion and Society, 2025)
This research explores the concept of Asbab al-Nuzul (occasions of revelation) and its crucial role in understanding the contextual meanings of the Qur'anic verses. It critically examines the authenticity of narrations attributed to the causes of revelation and identifies the presence of fabricated (mawdu‘) reports that have crept into Islamic literature over time. The study employs a rigorous methodological approach, analyzing classical and contemporary sources to distinguish between reliable and unreliable narrations. It highlights the criteria used by scholars of Hadith and Tafsir in authenticating reports and evaluates the impact of fabricated narrations on Qur'anic interpretation and Islamic thought. The findings underscore the necessity of scholarly vigilance and methodological soundness to preserve the integrity of Qur'anic exegesis and to prevent the misuse of weak or fabricated traditions. This study contributes to the broader field of Qur'anic studies by providing a nuanced understanding of the challenges and responsibilities in interpreting divine revelation. Keywords: Asbab al-Nuzul, contextual meanings, Methodological, Gabricated narrations.